Cognitive event-related potentials and oscillations in the subthalamic nucleus - Rektor, Ivan; Baláz, Marek; Bocková, Martina (Neuro-degenerative diseases, 2010)
BACKGROUND: The cognitive role of the subthalamic nucleus (STN) remains largely unknown. METHODS/RESULTS: A modified protocol with a dual task elicited local field event-related potentials (ERPs) within the STN. No generators of ERPs were elicited by the standard oddball protocol in the STN (at variance with recordings from the putamen, caudate and pallidum). Repetitive transcranial magnetic stimulation (rTMS) over the right inferior frontal cortex caused a shortening of latencies of ERPs in standard and dual protocols. No changes were observable after the rTMS over the dorsolateral prefrontal cortex and sham stimulation. In the STN, only the tasks with an increased demand on executive functions produced the alpha-/beta-event-related desynchronization/synchronization in visuomotor tasks with single letters writing. CONCLUSION: Our results indicate a specific, task-related involvement of the STN in the cognitive activities. Cognitive processing in the STN is possibly processed via hyperdirect cortico-STN pathway. Certain effects of deep brain stimulation surgery on cognitive performance could be explained by a direct effect on 'cognitive' parts of the STN.
Keywords: kognice; periodicita; Psychoacoustics; Biophysics; biofyzika; funkční lateralita; evokované potenciály; Parkinsonova nemoc; lidé; Evoked Potentials; Transcranial Magnetic Stimulation; Subthalamic Nucleus; Periodicity; nucleus subthalamicus; akustická stimulace; Cognition; Acoustic Stimulation; neuropsychologické testy; Humans; elektromyografie; Electroencephalography; Parkinson Disease; Neuropsychological Tests; elektroencefalografie; transkraniální magnetická stimulace; Functional Laterality; psychoakustika; Electromyography